Characterization and target gene analysis of microRNAs in the antennae of the parasitoid wasp Microplitis mediator. (24th July 2020) - Shan, Shuang; Wang, Shan‐Ning; Song, Xuan; Khashaveh, Adel; Lu, Zi‐Yun; Dhiloo, Khalid Hussain; Li, Rui‐Jun; Gao, Xi‐Wu; Zhang, Yong‐Jun
Abstract: MicroRNAs (miRNAs), a class of non‐coding single‐strand RNA molecules encoded by endogenous genes, are about 21–24 nucleotides long and are involved in the post‐transcriptional regulation of gene expression in plants and animals. Generally, the types and quantities of miRNAs in the different tissues of an organism are diverse, and these divergences may be related to their specific functions. Here we have identified 296 known miRNAs and 46 novel miRNAs in the antennae of the parasitoid wasp Microplitis mediator by high‐throughput sequencing. Thirty‐three miRNAs were predicted to target olfactory‐associated genes, including odorant binding proteins (OBPs), chemosensory proteins, odorant receptors (ORs), ionotropic receptors (IRs) and gustatory receptors. Among these, 17 miRNAs were significantly highly expressed in the antennae, four miRNAs were highly expressed both in the antennae and head or wings, while the remaining 12 miRNAs were mainly expressed in the head, thorax, abdomen, legs and wings. Notably, miR‐9a‐5p and miR‐2525‐3p were highly expressed in male antennae, whereas miR‐1000‐5p and novel‐miR‐13 were enriched in female antennae. The 17 miRNAs highly expressed in antennae are likely to be associated with olfaction, and were predicted to target one OBP (targeted by miR‐3751‐3p), one IR (targeted by miR‐7‐5p) and 14 ORs (targeted by 15 miRNAs including miR‐6‐3p, miR‐9a‐5p, miR‐9b‐5p, miR‐29‐5p, miR‐71‐5p, miR‐275‐3p, miR‐1000‐5p, miR‐1000‐3p, miR‐2525‐3p, miR‐6012‐3p, miR‐9719‐3p, novel‐miR‐10, novel‐miR‐13, novel‐miR‐14 and novel‐miR‐28). These candidate olfactory‐associated miRNAs are all likely to be involved in chemoreception through the regulation of chemosensory gene expression in the antennae of M. mediator .